International Journal of Control, Automation and Systems - Hong, Keum-Shik.; SpringerLink (Online service) (Bucheon / Seoul : Institute of Control, Robotics and Systems and The Korean Institute of Electrical Engineers : Imprint: Institute of Control, Robotics and Systems and The Korean Institute of Electrical Engineers, co-published with Springer.)
International Journal of Control, Automation and Systems is a joint publication of the Institute of Control, Robotics and Systems (ICROS) and the Korean Institute of Electrical Engineers (KIEE). The journal covers three closly-related research areas including control, automation, and systems. The technical areas include Control Theory Control Applications Robotics and Automation Intelligent and Information Systems The Journal addresses research areas focused on control, automation, and systems in electrical, mechanical, aerospace, chemical, and industrial engineering in order to create a strong synergy effect throughout the interdisciplinary research areas.
Keywords: Control engineering; Robotics; Mechatronics; Control, Robotics, Mechatronics